2014
DOI: 10.3390/catal4030276
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of m-Dinitrobenzene to m-Nitroaniline over Ru-SnOx/Al2O3 Catalyst

Abstract: Series catalysts of Ru-SnO x /Al 2 O 3 with varying SnO x loading of 0-3 wt% were prepared, and their catalytic activity and selectivity have been discussed and compared for the selective hydrogenation of m-dinitrobenzene (m-DNB) to m-nitroaniline (m-NAN). The Ru-SnO x /Al 2 O 3 catalysts were characterized by X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM) and hydrogen temperature-programmed reduction (H 2 -TPR) and desorption (H 2 -TPD). Under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…The maximum temperature of the reduction peak was slightly lower than that of Scheme 1 Simplified reaction scheme for hydrogenation of 1-iodo-4nitrobenzene to 4-iodoaniline using molecular hydrogen including side products formed by hydro-deiodination (for detailed reaction mechanism see e.g. ref [38]) bulk RuO 2 [42] and was similar to that obtained for Ru/Al 2 O [43]. This broad peak is mainly attributed to the reduction of oxidized Ru species which are formed on alumina surface during catalyst storage under ambient conditions.…”
Section: Catalyst Characterizationsupporting
confidence: 71%
See 1 more Smart Citation
“…The maximum temperature of the reduction peak was slightly lower than that of Scheme 1 Simplified reaction scheme for hydrogenation of 1-iodo-4nitrobenzene to 4-iodoaniline using molecular hydrogen including side products formed by hydro-deiodination (for detailed reaction mechanism see e.g. ref [38]) bulk RuO 2 [42] and was similar to that obtained for Ru/Al 2 O [43]. This broad peak is mainly attributed to the reduction of oxidized Ru species which are formed on alumina surface during catalyst storage under ambient conditions.…”
Section: Catalyst Characterizationsupporting
confidence: 71%
“…The amount of hydrogen consumed in the 2nd reduction was generally higher than in the 1st reduction (Table 1 indicates that the interaction between Ru and the promoter in these samples should be stronger compared to the other ones. Moreover, the amount of consumed hydrogen for these catalysts was significantly higher than the theoretical value necessary to reduce RuO 2 to metallic Ru revealing that partially Cu, Sn, or Fe oxide species [43] were also reduced by hydrogen. Reduction of bulk SnO 2 and of SnO 2 particles deposited on alumina occurred at temperatures higher than 600°C [42,45] and reduction of alumina supported Fe 2 O 3 starts at temperatures higher than 400°C [46].…”
Section: Catalyst Characterizationmentioning
confidence: 85%
“…However, these signals can be extracted using a similar approach as with Ru 3d and C 1s. Ru 3p are much broader than Ti 2p and there are no Ru signals below 461 eV [88–91] . This means that the Ti 2p signals up to 459 eV can be quantitatively assigned.…”
Section: Resultsmentioning
confidence: 96%
“…Cheng et al [31] doped a ruthenium catalyst with SnOx and reported an electronic interaction between Ru-SnOx due to an electron transfer from the Ru nanoparticles to SnOx, inducing an electron deficit state of ruthenium nanoparticles, which was favorable for the adsorption of the electropositive N-atom belonging to the reactant nitro group. The electron deficient state of ruthenium can also be favorable for the hydrogen adsorption, resulting in the production of more active hydrogen species.…”
Section: Resultsmentioning
confidence: 99%